Modelling of the Heated Water Spreading in Muara Karang Coastal Waters, Jakarta Bay - D.K. Mihardja; M.S. Fitriyanto; M.R. Putri (Institute for Research and Community Services (LPPM) ITB, 1999)
Abstract. Modelling of the heated water spreading in Jakarta Bay had been performed as a part of the study on cooling water circulation of Muara Karang Power Plant, North Jakarta. The results of the simulation described in this paper illustrated for cast season (August 1994), transitional season (November 1995), and west season (Januari 1996). The spreading of thermal water in Muara Karang coastal waters near the outlet canal of the power plant for each season and all tidal and wind conditions is dominantly influenced by discharge of cooling water that has maximum value of 35.1 m3/sec. In the far field area the spreading is directed by monsoon (wind-induced) currents and slightly influenced by tidal currents. Thermal water which spreads out from the outlet canal into coastal waters has a minimum area of about 58.60 hectares in transitional season at highest water level, and a maximum area of about 156 hectares in transitional season when water level goes to cbb. In general, the simulation results in the cast season are comparable to the observed data, while in the transitional season of cast-west season of cast-west season the and in the west season the model is still being verified. Pemodelan Penyebaran Air Hangat dari Pembangkit Listrik Tenaga Uap di Peraian Muara Karang, Teluk JakartaSari. Pemodelan sebaran panas di Teluk Jakarta merupakan salah satu bagian dari studi resirkulasi air pendingin PLTU Muara Karang, Jakarta Utara. Hasil simulasi pada makalah ini menggambarkan kondisi pada musim timur (Agustus 1994), musim peralihan (November 1995), dan musim barat (Januari 1996). Sebaran termal di perairan Muara Karang dekat saluran outlet PLTU untuk masing-masing musim dan semua kondisi pasang surut dan angina sangat dominan dipengaruhi oleh debit PLTU yang maksimum 35,1 m3/detik. Di daerah jauh, arah sebaran termal bergantung pada arus musim (pengaruh angin) dan sebagian dipengaruhi oleh pasang surut. Temperatur air panas yang keluar dari saluran outlet menyebar ke perairan dengan luas minimum 58,60 hektar pada musim peralihan pada saat air pasang maksimum, dan luas maksimum sekitar 156 hektar pada musim peralihan saat air menuju surut. Secara umum hasil simulasi pada musim timur yang dibandingkan dengan data lapangan hamper sesuai, sedangkan pada musim peralihan dari musim timur ke musim barat dan pada musim barat masih akan diverifikasi lebih lanjut.